PENGELOLAAN POTENSI DESA WISATA RUMADIAN KECAMATAN MANYEUW MELALUI KEBERLANJUTAN - Arianto Kerubun; Melissa Renjaan; Marselus Hungan (Journal of Tourism Destination and Attraction, 2022)
In 2020 the Southeast Maluku Tourism Office formed 25 tourist villages. The development of tourist villages is supported by natural, social, cultural, historical, and another potential. One potential village that has been developed into a tourist village is the village of Rahadian. Rumadian Village has the potential of natural mangrove forests, brown rice farming, sources of water, artificial tourism, cultural peculiarities and traditions, and historical tourism potential which can attract tourists to visit. In order to increase the tourism of Rumadian village through potentials owned, therefore a concept of managing the potential for tourism villages that refer to aspects of tourism resources management, human resource management, marketing village marketing management, and risk management. The purpose of the study was to analyze the management of tourist villages and to develop the concept of managing the potential of the tourist village of Rumadian, Kec. Manyeuw The research method used is qualitative. Data analysis uses qualitative descriptive analysis. The results showed that the management of each potential of tourist villages is not optimized in managing natural and cultural tourism resources, management of human resources, tourism resource management and do not have risk management. Furthermore, this research produced a concept of the tourist village management approach which contained important points to connecting aspects of tourism resources management, management of human resources, marketing, and risk management with village potential